2019
DOI: 10.1002/1873-3468.13476
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical analysis of a phosin fromStreptomyces chartreusisreveals a combined polyphosphate‐ and metal‐binding fold

Abstract: X‐ray crystallographic analysis of a phosin (PptA) from Steptomyces chartreusis reveals a metal‐associated, lozenge‐shaped fold featuring a 5–10 Å wide, positively charged tunnel that traverses the protein core. Two distinct metal‐binding sites were identified in which the predominant metal ion was Cu2+. In solution, PptA forms stable homodimers that bind with nanomolar affinity to polyphosphate, a stress‐related biopolymer acting as a phosphate and energy reserve in conditions of nutrient depletion. A single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…We observed that in all Streptomyces species, the pap–pitH1 operon is linked, and in opposite orientation, to the pstSCAB cluster and the ppk gene encoding the polyphosphate kinase ( Figure 2 ), a fact that has not been reported previously. In addition, the gene SCO4144, downstream of ppk , encodes a protein with 67% identity to the phosin PptA that binds metals and polyphosphate [ 81 ]. The protein encoded by SCO4144 contains all of the histidine residues characteristics of metal-binding proteins and the arginine residues for sulphate binding found in PptA.…”
Section: The Pap-pith1-pstscab-ppta-nuda-ppk Sumentioning
confidence: 99%
“…We observed that in all Streptomyces species, the pap–pitH1 operon is linked, and in opposite orientation, to the pstSCAB cluster and the ppk gene encoding the polyphosphate kinase ( Figure 2 ), a fact that has not been reported previously. In addition, the gene SCO4144, downstream of ppk , encodes a protein with 67% identity to the phosin PptA that binds metals and polyphosphate [ 81 ]. The protein encoded by SCO4144 contains all of the histidine residues characteristics of metal-binding proteins and the arginine residues for sulphate binding found in PptA.…”
Section: The Pap-pith1-pstscab-ppta-nuda-ppk Sumentioning
confidence: 99%
“…On its side, SLI_4383/PptA is described as a 388 AA long protein bearing a TTA leucine codon, possible target for bldA regulation [ 21 ] and possessing a conserved histidine alpha-helical domain (“CHAD” domain), considered as a polyphosphate binding module [ 19 , 20 ]. Interestingly, a comparison of the predicted protein product of SLI_4383 / pptA (GenBank entry EFD67904.1) to putative orthologues from other Streptomyces species revealed the presence of N-terminal extensions of various length whose extremity is highly conserved in almost all orthologues but which is missing in the protein of S. lividans as it is annotated at the Sanger center ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the recently determined crystal structure of S. chartreusis PptA [ 20 ], this N terminal region comprises part of the first α-helix of the protein fold. Since in the S. lividans genome (GenBank entry GG657756.1) a highly similar sequence is present immediately upstream of the designated pptA translational start codon, it seems likely that this codon was erroneously assigned to an internal GTG (Val) codon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations